This research examines rhetorical inimitability in the Holy Qur’an through the phenomenon of fronting and delaying in Surat Al-Mulk، as one of the important rhetorical features that reveals the precision of Qur’anic composition and the elevation of its st (Al-Farooq Journal of Sciences, 2026)
This research examines rhetorical inimitability in the Holy Qur’an through the phenomenon of fronting and delaying in Surat Al-Mulk، as one of the important rhetorical features that reveals the precision of Qur’anic composition and the elevation of its style. The study aims to clarify the concept of rhetorical inimitability، explain the linguistic and terminological meanings of fronting and delaying، and show their importance in constructing the Qur’anic sentence and highlighting intended meanings. The research adopts the descriptive analytical method by identifying examples of fronting and delaying in Surat Al-Mulk and analyzing their rhetorical and contextual implications. The study shows that fronting and delaying in the Qur’an do not occur randomly; rather، they follow a precise rhetorical wisdom connected to the context and the intended purpose of the verse. It also demonstrates that the most prominent purposes of this phenomenon in Surat Al-Mulk include specification، emphasis، glorification، alerting the listener، attracting attention، and achieving harmony between meaning and context. The research concludes that this phenomenon represents one aspect of Qur’anic inimitability، as it reveals the close connection between wording and meaning and confirms the persuasive and enduring power of Qur’anic expression.
Keywords: rhetorical inimitability، the Holy Qur’an، fronting and delaying، Surat Al-Mulk، Qur’anic rhetoric